2002
DOI: 10.1021/jf011249i
|View full text |Cite
|
Sign up to set email alerts
|

Sensory and Chemical Changes in Tomato Sauces during Storage

Abstract: The present work aimed to identify the key odorants of tomato sauces responsible for the flavor change during storage. Products made from paste or canned tomatoes were stored at 25 and 40 degrees C. Sensory properties and quantification of the key odorants were measured and correlated. Significant sensory changes appeared after 1 and 3 months at 25 degrees C in the respective dice and paste sauces (p < 0.01). The dice sauce was characterized by a steep loss of the sensory quality during the early storage and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 29 publications
0
6
0
1
Order By: Relevance
“…Damascenone was assessed as one of the most important volatile components of tomato paste samples in which it was found at an average concentration of 14 μg/kg, >10 times that in fresh tomatoes . The concentration of damascenone in tomato paste sauce increased during storage or mild heating . Similarly, the concentration of damascenone in strawberry homogenate heated to 100 °C for 30 min was >50 times higher than in the corresponding unheated sample, and the flavor dilution factor for damascenone was considerably higher in a heated, compared to an unheated, peach juice …”
Section: Damascenone As a Natural Product And As A Component Of Foods...mentioning
confidence: 99%
“…Damascenone was assessed as one of the most important volatile components of tomato paste samples in which it was found at an average concentration of 14 μg/kg, >10 times that in fresh tomatoes . The concentration of damascenone in tomato paste sauce increased during storage or mild heating . Similarly, the concentration of damascenone in strawberry homogenate heated to 100 °C for 30 min was >50 times higher than in the corresponding unheated sample, and the flavor dilution factor for damascenone was considerably higher in a heated, compared to an unheated, peach juice …”
Section: Damascenone As a Natural Product And As A Component Of Foods...mentioning
confidence: 99%
“…Landy et al . [ 42 ] also found that there was no correlation between mouthfeel and storage days but environmental conditions negatively influenced mouth feel.…”
Section: Resultsmentioning
confidence: 99%
“…A similar reducing trend in the overall acceptability of tomatoes during post-harvest changes was observed by Landy et al . [ 42 ]. Conclusively, carrot sauce having 70% carrot paste behaved well during the whole storage period with the good sensory and nutritional profile.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, MRI has been shown to be an effective method of evaluating the moisture distribution in boiled pasta. On the other hand, regarding pasta sauce quality, Landy et al (2002) reported the sensory and chemical changes in tomato sauce during storage, and Mirondo et al (2015) investigated how peel removal affects the flavor and viscosity of hot-and cold-break tomato juice and sauce.…”
Section: Introductionmentioning
confidence: 99%